Republik Turki Pasca Kemalis - H. Aminuddin Mamma (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
The purpose of writing this article is to determine the basics of the appeal to Mustafa Kemal Attaturk founded the secular state in Turkey, as well as the position of Islam as the secular post-modernization. A number of policies taken by Mustafa Kemal may be said so frontal and radical that invited a number of reactions. Religious consequences of the Kemalist reforms has always been a matter of debate that continues even to this day. Nevertheless secular reforms played a pivotal role in the rise of Islam back in Turkey and spawned a number of students from the class of intellectuals.